Molecular Microscope Diagnostic System in Patients after Kidney Transplantation—First Experience - Monika Beliančinová; Patrícia Kleinová; Tímea Blichová; Matej Vnučák; Karol Graňák; Katarína Kajová Macháleková; Ivana Dedinská (Biomedicines, 2024)
Background: The diagnosis of graft rejection relies on the identification of donor-specific antibodies along with histological findings. Borderline changes are particularly challenging, representing non-rejection findings in up to 70% of cases. The analysis aimed to compare the results of histopathological conclusions with the findings from examination using a molecular microscope, which assesses gene expression (whole-genome microarray chip technology). Methods: Molecular microscope examination (MMDx) was applied to twelve patients (six men and six women) who underwent either indication or protocol graft biopsy. Results: The average age of patients was 46.6 years ± 4.2 (average follow-up from kidney transplantation was 6.1 months ± 1.2). MMDx examination was performed during indication biopsy in 11 patients and protocol biopsy in 1 patient. A total of 33% of the findings matched and 50% did not. Finally, we present a case of a patient with acute cellular rejection findings without clinical and laboratory correlation, where the use of MMDx significantly altered the treatment strategy. Conclusions: MMDx examination is suitable for complementing patients with ambiguous histological findings and a clinical picture not corresponding to biopsy results. The limitations of MMDx include cost and its inability to evaluate the potential recurrence of the underlying kidney disease in the graft.